Measuring the organizational legitimacy of waste management companies in improving the level of services provided to Shah Alam household residents / Nor Farhana Mohamad Hafidz - Mohamad Hafidz, Nor Farhana (2022)
The price of development often comes with the upsurge of waste which has always been an ongoing issue that any country faces as a challenge, but the pandemic era of Covid-19 has now significantly contributed to a new emerging problem: pandemic essential wastes. Since the pandemic happened, face masks and sanitizer bottles made up of single use and disposable wear plastics have skyrocketed, and the ever-growing question becomes, what happens to all these wastes? This research aims to address this question by tackling waste management at its root source; the waste management companies. The research objective posed in this study are to examine the level of organizational legitimacy among waste management companies, determine the relationship of social environment characteristics, organizational characteristics and legitimacy management of waste management companies and to examine the mediating effect of organizational reputation in the relationship between social environmental characteristics, organizational characteristics and legitimacy management towards the organizational legitimacy of the waste management companies. A total of 510 respondents from the Shah Alam household areas were selected to execute the quantitative study. SPSS and PLS-SEM were both used to analyse the data and findings of this study. It was found upon data analysis, that there is in fact a high level of legitimacy for the waste management companies in Shah Alam and a significant positive relationship towards organizational legitimacy with social responsibility from social environmental characteristics, strategic behavior from organizational characteristics and gaining social support from legitimacy management. The mediating role of organizational reputation here has been established as supporting organizational legitimacy. This study has showcased that there is legitimacy ascribed to the waste management companies by the household residents of Shah Alam and highlights on the significance of the waste management companies’ social responsibility, their ability to behave strategically in implementing any waste management efforts as well as the importance of gaining social support in any collaborative initiatives of environmental sustainability. There has been new knowledge added to the existing literature and gap of knowledge that exists between legitimacy and waste management.